Pengaruh Model Pembelajaran Gallery Walk terhadap Pemahaman Konsep dan Sikap Gotong Royong Peserta Didik pada Materi Sistem Indra : (The Influence of The Gallery Walk Learning Model on Students’ Understanding of Concepts and Mutual Cooperation Attitudes in Sensory System Material) - Humairoh, Dewi Fatma; Permadani, Kurnia Galih; Darmawan, Ericka (BIODIK, 2024)
This research aimed to determine the effect of the gallery walk learning model on students' understanding of concepts and mutual cooperation attitudes in sensory system material at SMA Negeri 1 Grabag. This research used a quantitative approach with a quasi-experimental non-equivalent control group design method. This research was carried out at SMA Negeri 1 Grabag with a sampling technique using purposive sampling consisting of a control class, namely class XI F1, and an experimental class, namely class XI F2. The instruments used were multiple-choice test questions, attitude scales, and observation sheets. The research results show that the concept understanding value using the Man-Whitney U-test is 0.002 and the mutual cooperation attitude value using the Independent Sample T-test is 0.000. These data show the influence of implementing the gallery walk learning model on students' understanding of concepts and mutual cooperation attitudes. Learning using the gallery walk model can be used as a learning innovation to improve students' understanding of concepts and mutual cooperation attitudes. Abstrak. Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran gallery walk terhadap pemahaman konsep dan sikap gotong royong peserta didik pada materi sistem indra di SMA Negeri 1 Grabag. Penelitian ini menggunakan pendekatan kuantitatif dengan metode quasi eksperimen non equivalent control group design. Penelitian ini dilaksanakan di SMA Negeri 1 Grabag dengan teknik pengambilan sampel menggunakan purposive sampling yang terdiri atas kelas kontrol yakni kelas XI F1 dan kelas eksperimen yakni keals XI F2. Instrumen yang digunakan yakni soal tes pilihan ganda, skala sikap dan lembar observasi. Hasil penelitian menunjukkan bahwa nilai pemahaman konsep dengan uji Man-whitney u-test sebesar 0.002 dan nilai sikap gotong royong dengan uji Independent sampel t-test sebesar 0.000. Data tersebut menunjukkan bahwa terdapat pengaruh penerapan model pembelajaran gallery walk terhadap pemahaman konsep dan sikap gotong royong peserta didik. Melalui pembelajaran dengan model gallery walk dapat dijadikan sebagai inovasi pembelajaran untuk meningkatkan pemahaman konsep dan sikap gotong royong peserta didik.